EUS-guided celiac plexus neurolysis for pain in pancreatic cancer patients – a meta-analysis and systematic review. Issue 4 (4th July 2021) - Asif, Abuzar A.; Walayat, Saqib K.; Bechtold, Matthew L.; Revanur, Vakya; Puli, Srinivas R.
ABSTRACT: Background : Endoscopic ultrasound guided celiac plexus neurolysis (EUS- CPN) has been reported to be an effective way to help with pain in pancreatic cancer patient. The aim of our updated meta-analysis is to assess the efficacy of pain relief in patients with pancreatic cancer who underwent EUS guided neurolysis. Methods : Pooled proportions were calculated using both Mantel-Haenszel method (fixed effects model) and DerSimonian Laird method (random effects model). The heterogeneity among studies was tested using Cochran's Q test based upon inverse variance weights.  Results : Initial search identified 176 reference articles, of which 34 were selected and reviewed in detail. Sixteen studies that met the inclusion criteria were included in this analysis. The mean age of patients undergoing neurolysis was 56.31 ± 19.72 years. Number of males, N = 563 (57.4%), was higher than the number of females, N = 417 (42.5%). The pooled proportion of patients who showed pain relief with EUS-guided neurolysis was 71% (95% CI = 68–74). Bias calculated using Begg–Mazumdar was not significant ( p = 0.8). In a subgroup analysis, when comparing the central and bilateral techniques, the pooled proportion of patients with pain relief was 66% (95% CI = 61–71) and 57% (95% CI = 48–67), respectively. Conclusions : Our results show that EUS guided CPN could provide relief in as much as 70% of patients with central neurolysis technique having some edge over peripheral neurolysis. Further larger scale randomized controlled trials may further help to elaborate the efficacy of central vs peripheral neurolysis.